2017
DOI: 10.1002/ajpa.23272
|View full text |Cite
|
Sign up to set email alerts
|

Resource intensification and osteoarthritis patterns: changes in activity in the prehistoric Sacramento‐San Joaquin Delta region

Abstract: The temporal increase in hip osteoarthritis supports the hypothesis that there was an increasing need for greater logistical mobility over time to procure key resources away from the village sites. Additionally, the lack of sex differences in osteoarthritis prevalence may suggest that females and males likely performed similar levels of activity during these periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
14
0
3
Order By: Relevance
“…Weiss and Jurmain (2007) also suggested that a missing element in any study of biomechanical changes, especially those associated with OA, is subadult risk, with an interest in establishing juvenile age of onset, injury, and activity intensity. Thus, most recent research on OA, entheseal changes, and CSG was careful to use population-oriented approaches, factor in age at death and sex, and note if subadults were affected (Austin, 2017;Becker, 2017;Becker and Goldstein, 2017;Cheverko and Bartelink, 2017;Domett et al, 2017;Palmer et al, 2016;Schrader and Buzon, 2017).…”
Section: Prior Uses Of Oa Entheses and Csgmentioning
confidence: 99%
“…Weiss and Jurmain (2007) also suggested that a missing element in any study of biomechanical changes, especially those associated with OA, is subadult risk, with an interest in establishing juvenile age of onset, injury, and activity intensity. Thus, most recent research on OA, entheseal changes, and CSG was careful to use population-oriented approaches, factor in age at death and sex, and note if subadults were affected (Austin, 2017;Becker, 2017;Becker and Goldstein, 2017;Cheverko and Bartelink, 2017;Domett et al, 2017;Palmer et al, 2016;Schrader and Buzon, 2017).…”
Section: Prior Uses Of Oa Entheses and Csgmentioning
confidence: 99%
“…In this study, 25 total surfaces in six synovial joints (shoulder, elbow, wrist, hip, knee, and ankle) and one synovial and fibrous joint (sacroiliac) were scored for OA (Table 1). Using these data, we evaluated if there were any significant variations between the two stylistic groups, as these may translate into evidence of subsistence strategy-based repetitive motion differences (Becker, 2016;Becker, 2017;Bridges, 1991;Bridges, 1992;Bridges, 1995;Cheverko & Bartelink, 2017;Cope, Berryman, Martin, & Potts, 2005;Domett, Evans, Chang, Tayles, & Newton, 2017;Jurmain, 1999;Walker-Bone & Palmer, 2002;Weiss & Jurmain, 2007).…”
mentioning
confidence: 99%
“…El análisis de actividades se centró en la presencia de lesiones articulares asociadas a procesos no degenerativos (Britges 1992; Jurmain y Kilgore 1995; Resnick y Niwayama 1981, Burt et al 2013, Calce et al 2018, Cheverko y Bartelink 2017. Se distinguió entre la osteofitosis vertebral (OV, o Spondylosis deformans) y la osteoartritis (OA o artrosis) de las articulaciones sinoviales, incluyendo en esto último las facetas apofisarias de la parte posterior de la columna vertebral (Bridges 1992;Burt et al 2013;Jurmain y Kilgore 1995).…”
Section: Materials Y Métodounclassified